2013
DOI: 10.1074/jbc.a113.710128
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles for the C-terminal tail of the chemokine scavenger D6.

Abstract: PAGE 7977:The original version of Fig. 4 contained an error. The same image was used in the "wtD6" and "D6-Ala6" panels. We have now replaced the "D6-Ala6" panel with the correct image. This revision does not change the results or the interpretation of the data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Biochemically, ACKR2 is sulfated on N-terminal tyrosine residues and possesses a single N-terminal glycosylation site that is not required for function . In contrast to other chemokine receptors, which require ligand binding to induce phosphorylation, ACKR2 appears to be constitutively phosphorylated on the intracellular Cterminal domain, suggesting that it is in a permanently active configuration with regard to receptor internalization and recycling (McCulloch et al, 2008).…”
Section: B Ackr2 (Formerly D6 or Ccbp2)mentioning
confidence: 81%
“…Biochemically, ACKR2 is sulfated on N-terminal tyrosine residues and possesses a single N-terminal glycosylation site that is not required for function . In contrast to other chemokine receptors, which require ligand binding to induce phosphorylation, ACKR2 appears to be constitutively phosphorylated on the intracellular Cterminal domain, suggesting that it is in a permanently active configuration with regard to receptor internalization and recycling (McCulloch et al, 2008).…”
Section: B Ackr2 (Formerly D6 or Ccbp2)mentioning
confidence: 81%
“…While there is agreement that it enters cells via clathrin-coated pits (CCPs), the role of b-arrestins, which direct many G proteincoupled receptors to CCPs, is unclear. We have found that constitutive phosphorylation of a serine cluster in the C-terminus of D6 drives b-arrestins to the cell surface in D6-expressing cells, and controls intracellular trafficking itineraries, but we also showed that this is dispensable for chemokine scavenging [17]. Instead, in our hands, a helical region in the C-terminal tail adjacent to the seventh transmembrane helix was critical for scavenging [17].…”
Section: D6 Scavenges Chemokines In Vitromentioning
confidence: 46%
“…We have found that constitutive phosphorylation of a serine cluster in the C-terminus of D6 drives b-arrestins to the cell surface in D6-expressing cells, and controls intracellular trafficking itineraries, but we also showed that this is dispensable for chemokine scavenging [17]. Instead, in our hands, a helical region in the C-terminal tail adjacent to the seventh transmembrane helix was critical for scavenging [17]. Others reported that an acidic region at the other end of the C-terminal tail mediated constitutive interactions with b-arrestins and that these interactions were required for D6 internalization [14].…”
Section: D6 Scavenges Chemokines In Vitromentioning
confidence: 70%
“…The C-termini region of GPCRs has emerged as a critical structure in regulating several phases of their functions including dimerization, [67] expression, [68] signaling, [68 -70] trafficking, [71] and binding to regulatory proteins of the arrestin family. [72,73] Helix 8 is a distinctive long helical structure in the C-terminal region of several GCPRs including class A Rhodopsinlike family [63] and CRTH2.…”
Section: Ct-133 Binding Modulates Structural Dynamics Of C-terminal Tmentioning
confidence: 99%